Análisis retrospectivo de 9.023 informes de patología bucal en la Facultad de Odontología de la Universidad de Antioquia, Medellín, Colombia. 1972-2003 - Raúl Jiménez-G; Alejandro Díaz-L (Universidad de Antioquia, 2006)
9023 reports from the bio-analysis and immune detection laboratory were analyzed at the School of Dentistry of the University of Antioquia from the period of 1972 to 2003. A total of 5.890 reports corresponded to women (p< 0.001), 79% to people older than 36 years of age and 95% to people from the province of Antioquia , Colombia. The most common diagnosis were: fibrous augmentation due to trauma (11.2%); stomatitis due to ill adjusted dentures (7.4%); periapical inflammatory cysts (4.6%); piogenic granulomas (4.1%); squamous cellular carcinoma (4.0%); apical granulomas (3.7%); mucocele (3.0%); follicular cyst (dentígerous) (2.9%) and epithelium with dysplasia in white lesions of the leukoplakia type (2.2%). These lesions correspond to 43.1% of the total. 94% of the cases belonged to the following pathology groups: inflammatory lesions (26%); reactive or benign proliferative (25.5%); cysts and similar lesions (16.2%); benign tumors (8.9%); odontogenic tumors (3.3%), potentially malignant lesions (8.1%) and malignant neoplasia (6.1%). Oral pathology, considered specifically and by pathological groups, affected women more than men. The squamous cellular carcinoma and the epithelial dysplasia in lesions diagnosed as leukoplakia presented higher frequencies than expected.